An Analysis of Elementary School Students’ Number Sense in Solving Numerical Problems - Vivin, Meyta; Mariana, Neni; Solihin, Annas; Farman (MaPan : Jurnal Matematika dan Pembelajaran, 2025)
This study aims to analyze students’ number sense abilities in solving number problems at the elementary school level. The method used was quantitative descriptive with 22 fifth-grade students as subjects at SD Muhammadiyah 24 Surabaya. The instrument used was a diagnostic test based on number sense indicators, including estimation, calculation flexibility, and relationships between numbers. The analysis results show that most students (54.5%) are in the medium ability category, 27.3% in the low category, and only 18.2% in the high category. The average score per aspect shows that students are weakest in estimation (52%), while relationships between numbers are the most mastered aspect (68%). These findings indicate that students’ number sense abilities are still limited to procedural understanding and have not developed conceptually. Therefore, mathematics learning needs to be redesigned to emphasize the development of numerical intuition and contextual understanding of the meaning of numbers. This study recommends integrating exploration-based learning strategies, alternative strategy discussions, and logical estimation in the teaching and learning process in the classroom. Abstrak: Penelitian ini bertujuan untuk menganalisis kemampuan number sense siswa dalam menyelesaikan soal bilangan di tingkat sekolah dasar. Metode yang digunakan adalah kuantitatif deskriptif dengan subjek sebanyak 22 siswa kelas V di SD Muhammadiyah 24 Surabaya. Instrumen yang digunakan berupa tes diagnostik berbasis indikator number sense yang mencakup aspek estimasi, fleksibilitas berhitung, dan hubungan antarbilangan. Hasil analisis menunjukkan bahwa mayoritas siswa (54,5%) berada pada kategori kemampuan sedang, 27,3% dalam kategori rendah, dan hanya 18,2% dalam kategori tinggi. Rata-rata skor per aspek menunjukkan bahwa siswa paling lemah dalam estimasi (52%), sementara hubungan antarbilangan menjadi aspek paling dikuasai (68%). Temuan ini menunjukkan bahwa kemampuan number sense siswa masih terbatas pada pemahaman prosedural dan belum berkembang secara konseptual. Oleh karena itu, pembelajaran matematika perlu didesain ulang agar lebih menekankan pada pengembangan intuisi numerik dan pemahaman makna bilangan secara kontekstual. Penelitian ini merekomendasikan integrasi strategi pembelajaran berbasis eksplorasi, diskusi strategi alternatif, dan estimasi logis dalam proses belajar-mengajar di kelas.